Proses Penerbitan Dokumen Fumigasi pada Kapal Mt. Straits Dignity di Kantor Kesehatan Pelabuhan pada PT. Putra Samudera Inti Batam - Imanuel Rivaldo; Suparman Suparman; Irma Handayani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This paper discusses efforts to prevent plague disease in Indonesia through port fumigation. Using a descriptive qualitative method, the research revealed pest vectors on the MT. STRAITS DIGNITY ship and fumigation implementation challenges. It concluded that fumigation is the most effective method for pest control, with recommendations for ship crews to maintain cleanliness and Port Health Offices to conduct routine sanitation checks to minimize disease spread risks.